Social Media and Agropreneurial Development in Nigeria - Nwokeocha, Ifeanyi Martins (International Journal of Religion Education and Law, 2025)
Social media has emerged as a powerful tool for fostering agro-preneurial development in Nigeria, leveraging digital platforms to connect farmers, agribusinesses, and stakeholders along the agricultural value chain. The use of social media in the agricultural sector offers numerous benefits, including access to market information, networking opportunities, knowledge sharing, and entrepreneurship support, which can enhance productivity, profitability, and sustainability in the agribusiness sector. Social media platforms provide agro-preneurs in Nigeria with a direct and cost-effective channel to market their products and services to a broader audience, beyond traditional physical boundaries. By leveraging digital platforms such as Facebook, Instagram, Twitter, and WhatsApp, agribusiness stakeholders can showcase their offerings, share information about their farming practices, and engage with potential customers in real-time. This study examined social media and agro-preneurial development in Nigeria: an assessment. Three objectives were formulated for the study and qualitative research methods were also adopted to underscore divergent literatures published in journals, books, websites, internet, etc to establish a perspective on the study. The study concluded that embracing social media as a tool for communication, marketing, and networking, agro-preneurs in Nigeria can tap into a wealth of resources, connect with like-minded individuals, and access market insights that can propel their businesses forward. The digital ecosystem facilitates information sharing, skills development, and partnership opportunities, enabling agribusiness stakeholders to stay competitive, innovate, and adapt to changing market dynamics in today's fast-paced and interconnected world. The study recommended that to maximize the benefits of social media for agro-preneurial development in Nigeria, it is essential to invest in digital literacy programs aimed at equipping agribusiness stakeholders with the necessary skills to navigate social media platforms effectively.